Pengaruh Tarif Pajak Progresif, Kualitas Pelayanan, Sanksi, Kesadaran, Dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Bhegawati, Desak Ayu Sriary; Verawati, Yenny; Widyantari , Gusti Ayu Ratih (ISAS, 2023)
One of the most serious problems for economic policy makers is boosting taxpayer compliance rates. Non-compliance in paying motor vehicle taxes is of course a problem every year in almost all districts in Bali. Taxpayer compliance is influenced by various factors, one of which is progressive tax. Progressive taxes are expected to increase regional revenues. In addition to progressive taxes, service quality, sanctions, awareness, and tax knowledge can also trigger an increase in regional income. This study aims to determine the effect of progressive tax rates, service quality, sanctions, awareness, and tax knowledge on motor vehicle taxpayer compliance. The population in this study were all taxpayers at the UPTD Services and Retribution of the Province of Bali in Denpasar City so that a sample of 100 taxpayers was obtained using accidental sampling data determination techniques. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that progressive tax rates have a negative effect on motor vehicle taxpayer compliance at the UPTD Service and Retribution of the Province of Bali and service quality, sanctions, awareness, and tax knowledge have a positive effect on motor vehicle tax compliance at the UPTD Service and Retribution Province of the Province. Bali. This research can provide information about progressive tax rates, service quality, sanctions, awareness, and tax knowledge of motor vehicle taxpayer compliance, because this can affect increasing local revenue. Keywords: Progressive Tax Rates, Service Quality, Sanctions, Awareness , And Tax Knowledge